Effect of pioglitazone on vasopressor responses to adrenergic agonists and angiotensin II in diabetic and non-diabetic spontaneously hypertensive rats - Afzal, Sheryar; Sattar, Munavvar Abdul; Akhtar, Safia; Abdullah, Nor Azizan; Eseyin, Olorunfemi A.; Abdulla, Mohammed H.; Johns, Edward James (Faculty of Pharmacy, University of Karachi, 2018)
Pioglitazone, peroxisome proliferator-activated receptor (PPAR-γ) agonist, is a therapeutic drug for diabetes. Present study investigated the interaction between PPAR-γ and alpha adrenoceptors in modulating vasopressor responses to Angiotensin II (Ang II) and adrenergic agonists, in diabetic & non-diabetic Spontaneously Hypertensive Rats (SHRs). Diabetes was induced with an i.p injection of streptozotocin (40 mg/kg) in two groups (STZ-CON, STZ-PIO), whereas two groups remained non diabetic (ND-CO, ND-PIO). One diabetic and non-diabetic group received Pioglitazone (10mg/kg) orally for 21 days. On day 28, the animals were anaesthetized with sodium pentobarbitone (60mg/kg) and prepared for measurement of systemic haemodynamics. Basal mean arterial pressure of STZ-CON was higher than ND-CON, whereas following pioglitazone treatment, MAP was lower compared to respective controls. MAP responses to i.v administration of NA, PE, ME and ANG II were significantly lower in diabetic SHRs: STZ-CON vs ND-CON (35%). Pioglitazone significantly decreased responses to NA, PE, ME and ANG II in ND-PIO versus ND-CON by 63%. Responses to NA and ANG II were significantly attenuated in STZ-PIO vs. ND-PIO (40%). PPAR-γ regulates systemic hemodynamic in diabetic model and cross-talk relationship exists between PPAR-γ and α1-adrenoceptors, ANG II in systemic vasculature of SHRs.